Placenta Accreta Spectrum: Biomarker Discovery Using Plasma Proteomics. Issue 2 (June 2021) - Shainker, S.A.; Silver, R.M.; Modest, A.M.; Hacker, M.R.; Hecht, J.L.; Salahuddin, S.; Dillon, S.T.; Ciampa, E.J.; D'Alton, M.E.; Otu, H.H.; Abuhamad, A.Z.; Einerson, B.D.; et al.
Abstract : ( Am J Obstet Gynecol . 2020;223:433.e1–14) Placenta accreta spectrum (PAS), which includes placenta accreta, placenta increta and placenta percreta, often leads to hysterectomy and large-volume maternal hemorrhage and is a major cause of maternal mortality and morbidity. While maternal outcomes can be improved with planning after an accurate diagnosis, more than 50% of pregnancies complicated by PAS are not diagnosed prior to delivery. A method of reliable, early diagnosis of PAS is needed to improve maternal outcomes. This study used a novel aptamer-based platform for biomarker discovery to explore whether women who experience PAS have a unique protein signature in maternal plasma during the third trimester that may be used to diagnose PAS.